The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1210/jc.2009-1286
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and Mifepristone Regulate L-Type Amino Acid Transporter 2 and 4F2 Heavy Chain Expression in Uterine Leiomyoma Cells

Abstract: We present evidence that progesterone and its antagonist mifepristone regulate the amino acid transporter system LAT2/4F2hc in leiomyoma tissues and cells. Our findings suggest that products of the LAT2/4F2hc genes may play important roles in leiomyoma cell proliferation. We speculate that critical ratios of LAT2 to 4F2hc regulate leiomyoma growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Recently, Luo et al [89] defined L-type amino acid transporter 2 (LAT2) as a novel PR target gene. Progesterone significantly induces LAT2 mRNA levels, which is blocked by cotreatment with the PR antagonist mifepristone.…”
Section: Pathogenesis Of Uterine Leiomyomamentioning
confidence: 99%
“…Recently, Luo et al [89] defined L-type amino acid transporter 2 (LAT2) as a novel PR target gene. Progesterone significantly induces LAT2 mRNA levels, which is blocked by cotreatment with the PR antagonist mifepristone.…”
Section: Pathogenesis Of Uterine Leiomyomamentioning
confidence: 99%
“…Gene knockdown studies revealed that KLF-11 inhibits proliferation of leiomyoma cells and that its expression is significantly lower in leiomyoma tissues compared with adjacent myometrial tissues. Another novel progesterone receptor target gene identified by ChIP-cloning was the L-type amino acid transporter 2 (LAT2) [132]. Progesterone significantly induced LAT2 mRNA levels, which was blocked by cotreatment with RU486.…”
Section: Regulation Of Genes Associated With Proliferation and Apoptomentioning
confidence: 99%
“…Mifepristone selectively inhibits the formation and development of many tumor types and plays an anti-tumor role as an antagonist through progesterone and glucocorticoid receptors (Kacinski et al, 2001;Luo et al, 2009;Ligr et al, 2012). In this study, 10 mg/mL mifepristone and MMC treatment at different concentrations was applied to HeLa/MMC cells; mifepristone alone had no significant inhibitory effect on the development of HeLa/MMC cells, but both the inhibition rate and drug sensitivity of the cells increased after combination treatment with MMC, indicating that other than anti-tumor activity, mifepristone reverses the drug resistance of tumor cells to some extent.…”
Section: Discussionmentioning
confidence: 99%